1999
DOI: 10.1016/s0146-6380(99)00080-7
|View full text |Cite
|
Sign up to set email alerts
|

Phytotoxicity of ancient gaswork soils. Effect of polycyclic aromatic hydrocarbons (PAHs) on plant germination

Abstract: of ancient gaswork soils. Effect of polycyclic aromatic hydrocarbons (PAHs) on plant germination. Organic Geochemistry, Elsevier, 1999, 30 (8) ABSTRACTThe phytotoxicity of various contaminated soils was assessed by plant inventories on ancient industrial fields, and by phytotoxicity tests. Industrial fields are well colonised by numerous weedy plants. Phytotoxicity was tested with pure PAHs, ancient industrial soils, soil leaches, liquid tar and tar volatile compounds. Both field studies and toxicity tests sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
74
0
5

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(88 citation statements)
references
References 10 publications
6
74
0
5
Order By: Relevance
“…Exposures to FLT alone at concentrations lower than 10 mg/L did not result in significantly lower germination rate (7 days), but all concentrations of FLT alone resulted in significant reduction of germination vigor (3 days), indicating that FLT delayed germination of soybean seeds, as compared to controls. The result is consistent with those of previous studies on effects of FLT on pea, maize, lettuce, tomato and other species (Henner et al, 1999;Kummerová and Kmentová, 2004;Smith et al, 2006). Indices of growth such as plant height, biomass and leaf area are a function of growth of plants.…”
Section: Discussionsupporting
confidence: 92%
“…Exposures to FLT alone at concentrations lower than 10 mg/L did not result in significantly lower germination rate (7 days), but all concentrations of FLT alone resulted in significant reduction of germination vigor (3 days), indicating that FLT delayed germination of soybean seeds, as compared to controls. The result is consistent with those of previous studies on effects of FLT on pea, maize, lettuce, tomato and other species (Henner et al, 1999;Kummerová and Kmentová, 2004;Smith et al, 2006). Indices of growth such as plant height, biomass and leaf area are a function of growth of plants.…”
Section: Discussionsupporting
confidence: 92%
“…The shorter period of time between the contamination and planting in this treatment could have allowed diesel oil, which was hydrophobic, to cover the seeds, producing a barrier to the passage of water and possibly gases to the interior of the seed. According to Henner et al (1999), the more recent the contamination, the higher were the concentration of volatile compounds and water-soluble compounds, which were most detrimental to germination. In addition, saturation of the seed and gas exchange are the initial stages in the germination process (Labouriau, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…Achuba (2006) reported that toxic hydrocarbon molecules could inhibit the activities of amylase and starch phosphorylase and thereby affecting the assimilation of starch. Henner et al (1999) reported that petroleum hydrocarbons consisting of small molecules and those that are water soluble are more phytotoxic for the germination. However, there have been reports describing the species whose germination was not affected by the presence of oil in the ground (Adam and Duncan, 2002;Merkl et al, 2004;Gogosz et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…According to Henner, et al (1999) some volatile fraction with less than 3 rings are found in spent oil. These compounds are known to have severe inhibitory impact on germination of several plant species.…”
Section: Discussionmentioning
confidence: 99%